1984
DOI: 10.3109/10641968409044039
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Metabolic Effects of Cortisol and Deoxycorticosterone in Man

Abstract: We have previously shown that ACTH administration (1 mg/day) for 5 days raises systolic blood pressure (BP) by some 20 mmHg in both normotensive and hypertensive subjects, accompanied by hypokalaemia, urinary Na retention, a rise in fasting blood glucose and a fall in plasma renin concentration (PRC). In the present study cortisol and deoxycorticosterone (DOC) were infused for 5 days in 7 and 6 subjects respectively at rates appropriate for conditions of ACTH stimulation to determine whether the effects of ACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 7 publications
2
32
0
1
Order By: Relevance
“…13 Systolic but not diastolic or mean blood pressure increased in all 8 subjects, who were confirmed to be capsule-compliant (by plasma cortisol levels); the increase in blood pressure averaged 7 mm Hg. The increase in blood pressure was accompanied by other previously documented pleiotropic and plasma biochemistry alterations.…”
Section: Discussionmentioning
confidence: 99%
“…13 Systolic but not diastolic or mean blood pressure increased in all 8 subjects, who were confirmed to be capsule-compliant (by plasma cortisol levels); the increase in blood pressure averaged 7 mm Hg. The increase in blood pressure was accompanied by other previously documented pleiotropic and plasma biochemistry alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol may directly increase vascular resistance and intravascular volume to increase blood pressure (68,128,129). Glucocorticoids also cause sodium retention and plasma volume increase (129).…”
Section: Introductionmentioning
confidence: 99%
“…2 Second, exogenous cortisol administration has been consistently shown to result in an increase in blood pressure. [3][4][5][6] Third, glucocorticoids are being increasingly implicated in the regulation of blood pressure at several sites, including the vasculature, the kidneys and the brain. 1 Fourth, higher cortisol concentrations have been observed in normotensive young individuals with a positive family history of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Furthermore, experimental infusion of cortisol in normotensive men has been repeatedly shown to result in an increase in blood pressure. [3][4][5][6] However, the evidence that suggests that cortisol excess is a feature of population hypertension is less overwhelming. Most of the relevant epidemiological studies are small and have samples approximately p500, and not all have found positive associations between cortisol and high blood pressure.…”
Section: Introductionmentioning
confidence: 99%